Pelatihan Public Speaking dalam Pengembangan Jiwa Enterpeneur - A. Rivai Beta; Mahmud Al Chusairi; Syarif Hidayatullah; Muhammad Najib Adfani; Syahrul Mubarak (Pusat Riset dan Inovasi Nasional, 2022)
Public Speaking is a communication skill that must be possessed by every entrepreneur in order to be able to compete in the world of work. Of course, the importance of public speaking must be taught from an early age, so that one day they can be confident in public. The importance of imparting public speaking skills from an early age gave the idea to create community service activities with the theme of public speaking training in developing an entrepreneurial spirit. This activity aims to make students from an early age understand the importance of public speaking in the world of Entrepreneurs. It is hoped that from this activity the students at the Tahfidz Izzatul Qur'an As-adiyah Islamic boarding school will have public speaking skills that support the future in becoming entrepreneurs